Analisis Pengaruh Intensitas Modal dan Penghindaran Pajak terhadap Nilai Perusahaan - Catherine, Catherine (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to analyze whether company size, profitability, leverage, liquidity, activity ratio, capital intensity, and tax avoidance and their influences on firm value in consumer cyclicals and consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the period for year 2020 - 2022. The sample used was 67 companies with 201 data that met the criteria and the sampling method used was purposive sampling. In performing hypothesis tests, multiple regression analysis was used. The results of this research showed that leverage had a positive influence on firm value. Company size had a negative influence on firm value. Profitability, liquidity, activity ratio, capital intensity, and tax avoidance had no effect on firm value.